Modern Diagnosis and Treatment of Pneumonia in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents material for 2022-2023 on the study of the course of pneumonia in children. A brief overview of current data on the etiology, pathogenesis, diagnosis, and antibacterial therapy of pneumonia in children is presented. Especially in outpatient settings, serious problems of pediatrics are early diagnosis and rational therapy of pneumonia in children. It should be clarified that the etiology of diseases of the lower respiratory tract differs sharply in different age groups. The most common cause of community-acquired pneumonia (up to 50%) is S. pneumoniae, less common are such sticks as E.coli, Klebsiella spp., C.trachomatis, Mycoplasma, Ureaplasma. In children older than 5 years in the etiological structure of community-acquired pneumonia, along with S. rpeimopiae, the importance of Mycoplasma rpeimopiae increases. The algorithm for diagnosing community-acquired pneumonia includes febrile fever lasting > 3 days, cyanosis, shortness of breath in the absence of signs of bronchial obstruction, cough. Tachypnea is one of the best predictors of pneumonia in children of all ages. During physical examination — the presence of a shortening of the percussion sound in the affected area, bronchial or weakened breathing, sonorous small-bubbly or crepitating wheezes.